AGEING POPULATION AND ITS IMPLICATIONS FOR URBAN PLANNING IN SURABAYA CITY - Annisadina, Tristina; Fernanda, Bella (ipdn, 2024)
Surabaya is inevitably influenced by the global trend of an ageing population; thus, policymakers need to integrate this factor into the city's future planning. This research seeks to outline the forthcoming elderly demographic and suggest strategies that correspond with this emerging trend. This research employs a dual methodology, integrating numerical data analysis with descriptive insights. The methodology utilizes the cohort component projection approach alongside content analysis. Data was obtained through secondary surveys by extracting data from existing literature. The results indicate that by 2050, there will be a significant rise in the elderly demographic, which will directly impact the old-age dependency ratio, necessitating proactive measures to address this concern. The Surabaya City Government can pursue initiatives aligned with the Age-Friendly City concept, though enhancements across various dimensions of this framework are necessary beforehand. Keywords: Cohort Component Projection, Ageing Population, and Age-Friendly City.